Optimizing orthodontic anchorage: comparative evaluation of larger diameter, shorter length mini-implants for enhanced mechanical stability - Swapnil Junnarkar; Anand Sabane; Amol Patil; Meenal Tepan; Tanisha Rout; Sonakshi Sharma; Arati Gholap (Folia Medica)
Aim: We aim to assess and contrast the mechanical stability of two mini-implant designs, featuring larger diameters and shorter lengths, for orthodontic anchorage against a conventional group of implants. Materials and methods: Three groups of mini-implant underwent testing: the implants in Group 1 were 2.5 mm in diameter and 4 mm in length; the implants in Group 2 were 3 mm in diameter and 3 mm in length; and the conventional group implants were 1.3 mm in diameter and 7 mm in length. Both types were Abso Anchor mini-implants (Dentos Inc.). The implants’ mechanical stability was assessed using the maximum insertion torque (MIT), the maximum removal torque (MRT), and the angulated lateral displacement tests for compression and tension force vectors. Fourteen mini-implants of each design were used to measure MIT and MRT. Seven mini-implants of each design were tested for lateral displacement. Results: Torque tests - Group 2 mini-implants showed superior primary stability with higher MIT and MRT values compared to Group 1 and the conventional group implants. Lateral displacement tests - Group 2 mini-implants required significantly greater compressive force than those in Group 1 and the conventional group. Tension force for lateral displacements was similar between the three groups. Conclusion: Group 2 mini-implants, with larger diameters and shorter lengths, demonstrated superior primary stability over Group 1 implants. Despite the differences in compressive force, all three groups performed similarly under tension in lateral displacement tests.